2010
DOI: 10.1016/j.ejcts.2009.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of B-type natriuretic peptide for postoperative atrial fibrillation following pulmonary resection for lung cancer

Abstract: Preoperative BNP level seems to be an appropriate predictor of AF after pulmonary resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 28 publications
1
36
1
4
Order By: Relevance
“…The overall BNP pattern appears somewhat biphasic. This is consistent with findings by Nojiri et al [22] in a study designed to evaluate the association between BNP secretion and postoperative atrial fibrillation. They reported a biphasic BNP pattern in a series of 80 patients with lung cancer submitted to pulmonary resection (not pneumonectomy).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overall BNP pattern appears somewhat biphasic. This is consistent with findings by Nojiri et al [22] in a study designed to evaluate the association between BNP secretion and postoperative atrial fibrillation. They reported a biphasic BNP pattern in a series of 80 patients with lung cancer submitted to pulmonary resection (not pneumonectomy).…”
Section: Discussionsupporting
confidence: 92%
“…Its association with heart failure, atrial fibrillation [22,23] and other cardiac or infective complications following pulmonary resection [24] is well documented. Elevated BNP levels are associated with primary pulmonary hypertension and this marker can distinguish heart failure from other causes of dyspnoea more accurately than left-ventricular (LV) ejection fraction and ANP level [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Thus far, an accumulating body of published data has illustrated that increased levels of natriuretic peptides predict postoperative major adverse clinical events, in general, and specifically PAF, both in cardiac and noncardiac surgery. 5,13,14,[46][47][48][49][50] The mechanisms underlying the link between high NT-proBNP values and increased PAF risk remain unclear. Natriuretic peptides may increase with chronic conditions that include aging, atrial fibrosis, and inflammation-factors also known to contribute to PAF occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…There are however conflicting reports about the reduction in postsurgical complications due to VATS [16] [17] [18], as well as other reports about reduction of postoperative AF thanks to thoracic epidural anesthesia in the setting of cardiovascular surgery. Further research on these issues is needed, and such studies may benefit by incorporating preoperative atrial natriuretic peptide and B-type natriuretic peptide, which Nojiri et al [19] reported could be a predictive factor for the occurrence of postoperative AF.…”
Section: Discussionmentioning
confidence: 99%